An 800 nm driven NaErF4@NaLuF4 upconversion platform for multimodality imaging and photodynamic therapy. Issue 26 (25th April 2018) - Li, Qiqing; Li, Xiaodan; Zhang, Li; Zuo, Jing; Zhang, Youlin; Liu, Xiaomin; Tu, Langping; Xue, Bin; Chang, Yulei; Kong, Xianggui
Abstract : The newly developed NaErF4 system offers a new strategy to design excellent theranostic nanoplatform for multimodality imaging-guided therapy. Abstract : Multimodality imaging-guided therapy based on lanthanide-doped upconversion nanoparticles (UCNPs) has become a trend in cancer theranostics. However, the overheating effect of 980 nm excitation in photodynamic therapy (PDT) and the difficulties in optimizing multimodality imaging integration within a single particle are still challenges. Herein, 800 nm driven NaErF4 @NaLuF4 UCNPs have been explored for optimized multimodality imaging and near-infrared (NIR) triggered PDT. Our results confirmed that the optimal ∼5 nm shell thickness can well balance the enhancement of upconversion luminescence and the attenuation of energy transfer efficiency from Er 3+ towards a photosensitizer, to achieve efficient production of singlet oxygen ( 1 O2 ) for PDT under 800 nm excitation. Furthermore, the as-obtained NaErF4 @NaLuF4 UCNPs showed effective and applicable performance for upconversion luminescence (UCL) imaging, X-ray computed tomography (CT), and high-field T 2 magnetic resonance imaging (MRI). This nanomaterial can serve as an excellent theranostic agent for multimodality imaging and image-guided therapy.